PERAN MAHASISWA KKN DALAM MENDORONG DIGITALISASI UMKM MELALUI PENERAPAN QRIS DI DESA SEMPAJAYA - Sapri; Nirina Triazi; Muhammad Nur Tondi; Aminuddin Harahap; Sella Febrianti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to describe the macro context of QRIS development and UMKM digitalization, link it to KKN program practices, and identify QRIS implications for local economic independence in Sempajaya Village, while providing practical recommendations for effective KKN mentoring models. It employs a descriptive qualitative approach with strategic case studies on two UMKM sites (mie sop stall and kede), using passive participant observation over 2 days, structured observation sheets, semi-structured interviews, secondary data from sales documents, and Miles-Huberman analysis for data reduction, display, and verification. Key results show 70 UMKM routinely using QRIS post-program, a 40% rise in non-cash transactions, transaction time reduced from 30 to under 10 seconds, 50% fewer calculation errors, and 25-30% income increase with improved financial inclusion.